Peran Media Sosial Dalam Memasarkan Produk Olahan Ud.Bolu Salak Kenanga Di Kota Padangsidimpuan - Andryan Syaputra; Nur Ahmadi Bi Rahmani (Jurnal Ekonomi dan Bisnis Digital, 2023)
The aim of this research is to determine the extent of the role of social media as a tool to improve marketing of UD processed products. Bolu Salak Kenanga in Padangsidimpuan City. This research uses descriptive qualitative research. The data sources used in this research are primary data sources and secondary data. Data collection techniques were carried out using observation, interviews and documentation methods. Data analysis in this research is data reduction, data presentation, drawing and conclusions. The research results show that the use of social media as a promotional medium is very important for improving culinary business product marketing (MSMEs) in online marketing, especially culinary businesses that are relatively small.